2022
DOI: 10.1101/2022.08.09.503381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coxsackievirus B3 elicits a sex-specific CD8+T cell response in female mice

Abstract: Sex is a significant contributor to the outcome of human infections. Males are frequently more susceptible to viral, bacterial, and fungal infections, which is often attributed to a weaker immune response. In contrast, a heightened immune response in females enables better pathogen elimination but leaves females more predisposed to autoimmune diseases. Unfortunately, the underlying basis for sex-specific immune responses remains poorly understood. Here, we show a sex-specific difference in the CD8+ T cell resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…We previously found that splenic CD4 + and CD8 + T cells expand at 5dpi in orally CVB3-infected female Ifnar -/- mice but not infected male Ifnar -/- mice (30). In contrast to antigen-experienced CD8 + T cells that increase as early as 5 dpi, we found that splenic antigen-experienced CD4 + T cells from female mice do not increase until 15 dpi (30).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously found that splenic CD4 + and CD8 + T cells expand at 5dpi in orally CVB3-infected female Ifnar -/- mice but not infected male Ifnar -/- mice (30). In contrast to antigen-experienced CD8 + T cells that increase as early as 5 dpi, we found that splenic antigen-experienced CD4 + T cells from female mice do not increase until 15 dpi (30).…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that splenic CD4 + and CD8 + T cells expand at 5dpi in orally CVB3-infected female Ifnar -/- mice but not infected male Ifnar -/- mice (30). In contrast to antigen-experienced CD8 + T cells that increase as early as 5 dpi, we found that splenic antigen-experienced CD4 + T cells from female mice do not increase until 15 dpi (30). However, we hypothesized that splenic CD4 + T cells may be undergoing signs of early activation even though the upregulation of the cell surface expression of the surrogate makers, CD11a and CD49d, had not occurred.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations